Conversor híbrido para sistemas de iluminação com comunicação por luz visível - Loose, Felipe (2022)
This work considers a new proposal of light emitting diode (LED) driver with the function of visible light communication (VLC). VLC utilizes the light generated by LEDs for transmission of wireless data by modulating their current, which modulates their emitted light. The main hypothesis of this thesis centers on the idea that it is possible to attain high power efficiency while utilizing linear power amplifiers (LPAs) as part of an LED driver, through the confection of a hybrid converter. Thus, the solution aims to unite the high efficiency of switched power supplies with the high bandwidth capabilities of LPAs. The proposed circuit is capable of regulating the average level of the output current, for lighting purposes, while modulating the instantaneous values of such current, for communication purposes. A wide literature review on the subject is presented, regarding dual-purpose drivers for LEDs. Hence, through the content observed, and considering an LED linear model, a single-inductor dual output DC-DC converter is presented, which processes the power for both lighting and communications. The hypothesis is sustained through the design of a circuit prototype in the form of a buck converter working along with a class AB amplifier. A design methodology is presented, together with a Laplace model in order to address the adequate design of the voltages, currents and bandwidth of the system. Moreover, the prototype is put under tests based on quantitative figures of merit, such as efficiency and error vector magnitude (EVM). The experimental results are compared with other similar works available in the literature. In conclusion, the prototype sustains the main hypothesis of this thesis showing a 94% efficiency, a 3,68 MHz bandwidth and a 6,05 megabits per second data rate capacity, while processing power from a 48 V DC bus, providing a 20 W output rated power to an LED load.